Acute flaccid myelitis in Europe between 2016 and 2023: indicating the need for better registration - Helfferich, Jelte; Calvo, Cristina; Alpeter, Ekkehardt; Andres, Cristina; Anton, Andres; Aubart, Melodie; Bova, Stefania Maria; Cabrerizo, Maria; von Eije, Karin; Fabiola, Stollar; Felipe, Ana; Iordanova, Ralitsa; et al. (EUR CENTRE DIS PREVENTION & CONTROL, 2025)
Background: Acute flaccid myelitis (AFM) is a rare polio-like condition affecting mainly children and characterised by severe, often persistent, weakness. It is one of several causes of acute flaccid paralysis (AFP), which manifests as acute onset of limb weakness and reduced muscle tone. Some non-polio enteroviruses (EV), such as EV-D68 may cause AFM. Little is known about AFM incidence in Europe.
Aim: We aimed to better understand AFM incidence, aetiology and current surveillance policies in Europe.
Methods: In 28 countries, members of the European non-polio enterovirus network (ENPEN) and a newly established AFM network of clinicians under ENPEN received a survey asking them how AFM surveillance was performed in their countries in 2016-2023 and the numbers of AFM cases including those diagnosed with EV-D68 infection during this period.
Results: Surveillance information was obtained for 16 countries. In eight countries, AFP surveillance initiated for poliomyelitis eradication was still ongoing, while non-polio AFM cases were only systematically reported in Norway. The survey revealed 130 AFM cases for 14 countries, with 48 (37%) EV-D68-laboratory-confirmed. Among the AFM cases, 70% (n = 91) occurred in 2016, 2018 and 2022, when EV-D68 circulation increased.
Conclusions: This report provides some indication of AFM case numbers in Europe since 2016. However, as 15 of 16 countries with AFM monitoring information lacked structural AFM surveillance, numbers should be interpreted with caution. Knowing AFM incidence matters to determine its impact and detect future outbreaks. Thus, the newly established clinical network will develop a European AFM repository.